Engineering Innovation : From idea to market through concepts and case studies - Legum, Benjamin M.; Stiles, Amber R.; Vondran, Jennifer L. (De Gruyter Textbook, 2019)
Engineering Innovation is an overview of the interconnected business and product development techniques needed to nurture the development of raw, emerging technologies into commercially viable products. This book relates Funding Strategies, Business Development, and Product Development to one another as an idea is refined to a validated concept, iteratively developed into a product, then produced for commercialization. Engineering Innovation also provides an introduction to business strategies and manufacturing techniques on a technical level designed to encourage passionate clinicians, academics, engineers and savvy entrepreneurs. Offers a comprehensive overview of the process of bringing new technology to market. Identifies a variety of technology management skill sets and management tools. Explores concept generation in conjunction with intellectual property development for early-stage companies. Explores Quality and Transfer-to-Manufacturing.